UJI EFEKTIVITAS EKSTRAK ETANOL DAUN KASTURI (Mangifera casturi Kosterm) TERHADAP PENURUNAN KADAR ASAM URAT SECARA IN VIVO - Nur Mahdi; Hajatul Kamaliah; Raisha Hamiddani Syaiful; Okta Muthia Sari; Aditya Maulana Perdana Putra (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Gout is a non-communicable disease whose prevalence continues to increase, particularly among the elderly. The treatment using medicinal plants has become widely known to the public, one of which involves kasturi leaves, which are known to contain flavonoids, alkaloids, and tannins that are potentially effective as antihyperuricemic agents. This study aimed to evaluate the effectiveness of extract of kasturi leaves in reducing uric acid levels in Mus musculus. The research employed a true experimental design with a pre-and post-test control group approach. A total of 25 mice were divided into five groups: a negative control group (Na-CMC 1%), a positive control group (allopurinol), and three treatment groups with extract doses of 3 mg/kgBW, 6 mg/kgBW, and 9 mg/kgBW. Hyperuricemia was induced using chicken liver for 7 days. Afterward, the extract was administered for another 7 days, and uric acid levels were measured before and after treatment using the Glucometer tool. The data were analyzed using ANOVA. The results showed that dose 1st reduced uric acid by 21.56%, dose 2nd by 27.15%, and dose 3th by 38.88%. Based on these findings, the ethanol extract of casturi leaves was proven effective in lowering uric acid levels and comparable to allopurinol. Statistically, dose III had a significantly different effect from the negative control and was not significantly different from allopurinol (p> 0.05). It can be concluded that the ethanol extract of casturi leaves at a dose of 9 mg/gBW has the most effective antihyperuricemic activity. The calculated ED50 value was 13.20 mg/gBW.